Word imageability and orthographic neighbourhood effects on memory: a study in free recall and recognition. Issue 6 (3rd July 2021) - Ballot, Claire; Mathey, Stéphanie; Robert, Christelle
ABSTRACT: This study investigated the effects of word imageability and orthographic neighbourhood size, as well as their combined effects, in free recall and recognition memory. A total of 45 young adults performed recall and recognition tasks on the same word materials. Word imageability and orthographic neighbourhood size were orthogonally manipulated across four word conditions: low-imageability words – high N, saveur [ flavor ], low-imageability words – low N, total [ total ], high-imageability words – high N, carré [ square ] and high-imageability – low N, nuage [ cloud ]. The results show that word imageability facilitates memory performance in both free recall and recognition tasks, while the effect of orthographic neighbourhood size was exhibited only in the recognition task. Finally, the orthographic neighbourhood effect was found to depend on word imageability. The implications of the results are discussed according to semantic and orthographic word characteristics with regard to the memory processes involved in free recall and recognition tasks.